INTRINSIC MOTIVATION AND EXTRA-ROLE BEHAVIOR: EXAMINING THE IMPACT OF VOLUNTEERING MEANINGFULNESS ON ORGANIZATIONAL CITIZENSHIP AMONG SARAWAK CIVIL SERVANTS - Sahari, Shahrizul Amizan; Singh, Kuldip; Junaidi, Noni Harianti (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Recent reforms in Sarawak’s civil service have replaced pension benefits with a contribution-based scheme for new hires, raising concerns about equity, morale, and retention. This study explores whether Volunteering Meaningfulness (VM) influences Organizational Citizenship Behavior (OCB) among civil servants in this changing policy environment. Guided by equity theory and intrinsic motivation literature, survey data were collected and analyzed to examine the relationship between VM and OCB. The results show that employees who find volunteering meaningful are more likely to engage in positive, discretionary workplace behaviors. These findings suggest that promoting meaningful voluntary activities can help sustain motivation and commitment despite structural changes. The study contributes to public sector research by highlighting the role of intrinsic motivation in shaping workplace behavior.